HIV-related stigma: effects on health outcomes and directions for stigma-focused interventions - Akınkoç, İlayda and Gökengin, Deniz and Turan, Bülent (Acta Medica, 2025)
HIV-related stigma is a widespread experience among HIV-affected individuals that may have an impact on the well-being of both people living with HIV (PLWH) and associated individuals. This review examines the multifaceted nature of HIV-related stigma by summarizing its dimensions. Furthermore, it discusses how different dimensions of HIV-related stigma and intersectional stigma due to co-existing stigmatized conditions can lead to differential effects on the mental and physical health outcomes of PLWH. The scope of this review consists of the associations between HIV-related stigma and mental health challenges of depression and anxiety, as well as substance use, with a focus on the cognitive behavioral underpinnings, social isolation, and health behaviors of PLWH. On the other hand, the interplays between HIV-related stigma and immunological parameters, such as CD4 counts and viral loads, were discussed, which may have an effect through behavioral and non-behavioral pathways. This review also discusses possible stigma-informed policies and interventions with a multi-level approach. Specifically, it suggests that the focus of structural-level interventions can constitute policy regulations to ensure reducing HIV-related stigma and stereotype threats in organizational and legal settings. Stigma-informed intrapersonal interventions may focus on providing strategies that can target the cognitive and behavioral experiences of HIV-affected individuals through individual or group therapies. Lastly, interventions that focus on interpersonal and intergroup experiences can underline improving the quality of the contact and relationship between PLWH and HIV-negative individuals to challenge HIV-related stigma and improve the well-being of both populations.